Relação entre personalidade, satisfação e desempenho individual : um estudo exploratório com equipes ágeis de desenvolvimento de software - Dias, Alessandro Valério (2016)
This study is an exploratory study on the individual characteristics of the Task-Technology Fit model (TTF), created by Goodhue (1995), through the search for relationships between personality, job satisfaction and performance in the agile methodologies scenario. The study was conducted by applying a socio-demographic questionnaire as well as structured and validated scales and inventories. The purpose of the application was to assess subjective and individual aspects and also obtain material to find the relationship between the objective personality profiles with job satisfaction and performance of individuals working with agile methods. To this end, there were assessed: personality through the Factorial Personality Inventory II (IFP-II; RUDDER; RABELO; ALVES, 2014); satisfaction evaluation at work through the implementation of Satisfaction Scale at Work (Siqueira, 1995); evaluation of symptoms of burnout by applying the Maslach, Jackson and Leiter (1996) instrument called the Maslach Burnout Inventory (MBI), translated in Brazil by (Tamayo, 1997); and performance evaluation through performance measurement issues by Chung, Lee and Kim (2014). The sample consisted of 87 individuals from teams studying agile methods or working in projects conducted by adoption of agile methods (FOWLER, BECK, 2000; BECK, 2001; Schwaber, SHUTERLAND, 2015), and the teams were selected in an emancipatory way. Although the study use quantitative data, the purpose is to qualitatively understand the phenomenon studied. The result were four distinct personality profiles that differ significantly from each other in several characteristics analyzed, named according to the emerging profiles from the cluster analysis: consume dream, bellicose energetic, low profile and negative resistant. Of these four, assuming that agile methods represent a new way of organizing work teams and that they contribute not only for software development, we suggest the first profile as the most adjusted. In addition, there are some other findings, are raised limitations of the study and pointed out future directions.